Wernicke’s Encephalopathy: An Unusual Consequence of the Acquired Immune Deficiency Syndrome—Case Report and Literature Review - Timothy R. Larsen; Dritan Dragu; Michael Williams (Case Reports in Medicine)
Introduction. Wernicke’s encephalopathy is a well-described syndrome characterized by the classic triad of confusion, ataxia, and ophthalmoplegia. Wernicke’s encephalopathy results from thiamine (vitamin B1) deficiency. Common causes include alcoholism and gastric disorders. Wernicke’s has been described in patients with acquired immune deficiency syndrome (AIDS); however, given these patients’ immunosuppressed state, the diagnosis of Wernicke’s encephalopathy is not apparent. Case Presentation. A 31-year-old previously healthy male presented to the ER complaining of progressive dyspnea. Workup revealed HIV/AIDS and PCP pneumonia. He was treated and improved. On day 14 he became confused and developed nystagmus and ataxia. Considering his immunocompromised state, infectious and neoplastic etiologies topped the differential diagnosis. CT head was negative. Lumbar puncture was unremarkable. Brain MRI revealed increased T2 signal in the medial thalamus bilaterally. Intravenous thiamine was administered resulting in resolution of symptoms. Discussion. The classic triad of Wernicke’s encephalopathy occurs in 10% of cases. When immunosuppressed patients develop acute neurologic symptoms infectious or neoplastic etiologies must be excluded. However, given the relative safety of thiamine supplementation, there should be a low threshold for initiating therapy in order to reverse the symptoms and prevent progression to Korsakoff dementia, which is permanent.